Effects of Scrophularia ningpoensis Hemsl. on Inhibition of Proliferation, Apoptosis Induction and NF-κB Signaling of Immortalized and Cancer Cell Lines - Thomas Efferth; Xiao Shen; Henry Johannes Greten; Tolga Eichhorn (MDPI AG, 2012)
Scrophularia ningpoensis has been used in China for centuries as a herbal tea to treat various diseases. Based on the numerous animal studies on its pharmaceutical effects and the long time clinical experiences, we studied the molecular and cellular mechanism underlying the bioactivity of aqueous extract of Scrophularia and its isolated compounds. Seven isolated compounds, unlike Scrophularia extract, failed to induce cytotoxicity on HaCaT cells, but their combination improved the effect of extract. Tumor cell line selectivity was not observed, when we studied its cytotoxic effect on melanoma cell lines. The apoptotic and anti-inflammatory effects of Scrophularia extract have been demonstrated on HaCaT cells. The extract induced those effects potentially through affecting the MAPK pathway and inhibition of the NF-κB pathway, Microarray-based bioinformatical analyses on the compound acetoside from Scrophularia revealed a gene expression profile which confirmed our findings with the extract on proliferation inhibition, anti-inflammation and apoptosis. With DNA alkylation as major proposed mechanism of action, we assume acetoside as one of the active compounds in Scrophularia.